OPTIMALISASI POTENSI PENDAPATAN MELALUI INOVASI SI-ERPIN (SISTEM INFORMASI ENTERPRISE RESOURCE PLANNING INNOVATION) - Rivanthio, Tubagus Riko; Salim, Agus; Rumaizha, Riri; Ramdhani, Mardhiya (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
PT Dunia Sandang Pratama is a fabric supplier company experiencing difficulties monitoring orders, ensuring timely deliveries, and producing accurate financial reports. These challenges have an adverse impact on customer satisfaction and operational efficiency. Because of the acute urgency of these issues, this community service project is designed to develop an integrated ERP system with e-commerce functionality to overcome the existing problems, increase efficiency, expand market reach and provide more accurate information to management. This community service is aligned with the United Nations Sustainable Development Goals (SDGs), particularly in fostering innovation and narrowing the digital divide. The service team, comprising four lecturers and five students, employed the Scrum methodology, which is flexible and interactive, to observe, analyse and design the system in collaboration with the partner, PT Dunia Sandang Pratama. The project's initial phase has been completed, including developing e-commerce features and sales modules. The preliminary results indicate an increase in efficiency concerning order management and reporting. Implementing the ERP system has enhanced data accuracy, operational efficiency, and employee competence. From a quantitative perspective, order processing time has been reduced, the incidence of data errors has decreased, and company revenue has increased. From a qualitative standpoint, employee competence in ERP usage has also improved, positively impacting decision-making. In conclusion, the project has successfully supported the company's decision-making processes.